Degradation and mechanism analysis of protein macromolecules by functional bacteria in tobacco leaves - Jiang, Chuandong; Kong, Decai; Li, Yangyang; Sun, Jingguo; Chen, Zhenguo; Yang, Mingfeng; Cao, Shoutao; Yu, Cunfeng; Wang, Zengyu; Jiang, Jiazhu; Zhu, Chengguang; Zhang, Nan; et al. (Frontiers in Microbiology, 2024)
Tobacco, a crop of significant economic importance, is greatly influenced in leaf quality by its protein content.However, current processing parameters fail to adequately meet the requirements for protein degradation. Microorganisms show promising potential for protein degradation and quality enhancement in flue-cured tobacco preparationIn this study, we isolated and identified a protein-degrading microorganism, BSP1, from tobacco leaf surfaces as Bacillus subtilis using phylogenetic tree analysis based on 16SrDNA sequences. Application of BSP1 to tobacco leaves significantly enhanced crucial enzyme activities, thereby accelerating protein degradation during the curing process. Furthermore, comprehensive genomic, transcriptomic, and metabolomic analyses of tobacco leaves show that BSP1 promotes protein degradation by enhancing the diversity of the leaf surface microbial community and affecting the ubiquitin proteasome pathway. This study introduces innovative methods to effectively enhance tobacco leaf quality.